The marketability discount in Spanish valuation multiples: investors’ perception in listed companies versus private transactions - Rodríguez López, Ángel; Rubio Martín, Gracia (Journal of Business Economics and Management, 2019)
The aim of this paper is to assess the fair marketability discount (MD) in the Spanish market for valuation multiples comparing public versus private transactions. The study finds that to obtain MD it is necessary previously to control by a battery of factors that affects ratios’ prices such as industry, firm size, profitability, risk, year and also other characteristics about the buyer. The interactions of MD with each variable showed different investors’ perceptions about non marketability enterprises explaining MD. The valuation methodology applied in the research was a cross section of 824 public and private acquisitions in the Spanish market from the period 2006−2017. This work represents important evidence, in a more integrated vision than previous literature, for analysts and regulators stressing the necessity to apply MD in Spanish valuation processes based in listed multiples.